Alan Cyril Walker. 23 August 1938—20 November 2017. (21st December 2019) - Hlusko, Leslea J.; Ungar, Peter S.
Abstract : Colleagues often refer to Alan Walker as the Eric Clapton (one of the most influential musicians of the late twentieth century) of palaeoanthropology in recognition of the artistry of his science. His field discoveries filled major gaps in our knowledge of primate evolution, such as elucidating the Miocene world of Proconsul and finding the transitional 'Black Skull' of Australopithecus aethiopicus and the skeleton of a Homo erectus boy. In addition to discovering these remarkable fossils, Alan was essential in bringing a palaeobiological approach to the laboratory interpretation of their bony morphology. He used the relationships between form and function in living species as a baseline for understanding the past, he pioneered dental microwear analysis to infer diet and was an early-adopter of the use of microCT to explore the internal structure of primate ear bones. Beyond these scientific accomplishments, however, it was Alan's grace and generosity that truly set him apart from his peers. As the patriarch of an extensive intellectual family of students, postdocs and colleagues, Alan taught by example how to be intellectually creative, brave, meticulous, generous and kind. His legacy will long be felt in both the science and the culture of palaeoanthropology.